Segmental resection of distal ureter with termino‐terminal ureteric anastomosis vs bladder cuff removal and ureteric re‐implantation for upper tract urothelial carcinoma: results of a multicentre study. (25th February 2019) - Abrate, Alberto; Sessa, Francesco; Sebastianelli, Arcangelo; Preto, Mirko; Olivero, Alberto; Varca, Virginia; Benelli, Andrea; Campi, Riccardo; Sessa, Maurizio; Pavone, Carlo; Serretta, Vincenzo; Vella, Marco; et al.
Abstract : Objectives: To compare overall (OS), cancer‐specific (CSS), recurrence‐free survival (RFS) and postoperative renal function amongst patients with upper tract urothelial carcinoma (UTUC) of the distal (lower lumbar and pelvic) ureter, electively treated with segmental resection and termino‐terminal anastomosis (TT) vs bladder cuff removal and ureteric re‐implantation (RR). Patients and methods: A multicentre retrospective study, including 84 patients diagnosed with UTUC of the distal ureter and treated with TT or RR, is presented. The primary endpoint was to compare TT and RR in terms of OS, CSS and RFS. As a secondary outcome, we compared the postoperative creatinine values as an index of renal function in the two groups. Results: Of 521 patients with UTUC, 65 (77.4%) and 19 (22.6%) patients underwent RR and TT, respectively. Pre‐ and postoperative characteristics were not statistically different between the two groups. The median follow‐up period was 22.7 months. Patients treated with TT and those treated with RR did not have significantly different 5‐year OS, CSS or RFS (73.7% vs 92.3%, P  = 0.052; 94.7% vs 95.4%, P  = 0.970: and 63.2% vs 53.9%, P  = 0.489, respectively). No difference in postoperative creatinine variation emerged in association with the surgical technique ( P  = 0.411). Conclusion: Patients treated with TT or RR for UTUC showed comparable OS, CSS, RFS and postoperative renal function. Our data suggest that bladder cuff removal is not imperative in the treatment of distal ureteric UTUC, and TT can be a safe solution in selected cases.